Technical Condition Analysis of Mechanical Equipment of Yerevan Lake Hydro Facility - Sarukhanyan, Arestak; Kelejyan, Hovhannes; Sahakyan, Aram (Scientific Papers of National University of Architecture and Construction of Armenia, 2024)
The article analyzes the results of the study of the technical condition of the mechanical equipment of Yerevan Lake, and identifies risks and threats to their strength and stability. Instrumental measurements were conducted to check amortization condition of mechanical equipment to correctly evaluate their future operation degree. Based on detailed observations of supply cables of electromechanical equipment and main units of structures it was recommended to replace them or conduct rehabilitation works.